2021
DOI: 10.1021/acs.macromol.1c01754
|View full text |Cite
|
Sign up to set email alerts
|

Regularity of Deuteration in Linear Polyethylene Prepared by Saturation of Polycyclopentene over Homogeneous Catalysts

Abstract: When isotopically labeling polymer chains for small-angle neutron scattering (SANS), it is highly desirable to achieve even intra-and interchain distributions of deuterium (D), such that scattering centers are uniformly placed along and among the chains. A common approach to introduce D is to catalytically saturate an unsaturated precursor polymer with D 2 . Heterogeneous catalysts often induce net H/D exchange between the polymer and D 2 gas, yielding excess D on the polymer which is nonuniformly distributed;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The hydrogenated polymers were recovered by hot filtration, precipitated into methanol, and dried under vacuum overnight. Previous studies have repeatedly shown that hydrogenation over Pd/CaCO 3 under these conditions is not accompanied by chain rearrangements. , …”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The hydrogenated polymers were recovered by hot filtration, precipitated into methanol, and dried under vacuum overnight. Previous studies have repeatedly shown that hydrogenation over Pd/CaCO 3 under these conditions is not accompanied by chain rearrangements. , …”
Section: Methodsmentioning
confidence: 86%
“…The polymer solution was transferred to a 2 L Parr stainless steel reactor, and Pd/CaCO 3 was added at a 2:1 weight ratio of catalyst (including support) to the polymer. The reactor was charged with 400 psi of H 2 at room temperature and stirred at 130 °C for PCP or 100 °C for PB for 24 h, by which point saturation had reached more than 99.9% for PCP as determined by 1 H NMR spectroscopy 40 and more than 99% for PB as determined by FTIR spectroscopy. 36 The hydrogenated polymers were recovered by hot filtration, precipitated into methanol, and dried under vacuum overnight.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%